The seizuring canine patient. (2nd July 2019) - Phillips, Sarah
Abstract : Seizures are very common in dogs and cats — the estimated prevalence of canine idiopathic epilepsy is 0.6% in the first opinion canine population in the UK. Patients that seizure due to metabolic disturbances or poisonong can be treated short term until imbalances are corrected. This artical explores the many types of seizures, where they originate from, and the importance of nursing care for the neurological seizure patient.